Interference Management in LTE-Advanced Cooperative Relay Networks: Decentralized Transceiver Design With Channel Estimation - Mafuta, Armeline Dembo; Walingo, Tom; Takawira, Fambirai (IEEE access, 2019)
Wireless networks improve indoor communications by deploying femtocell networks into the macrocell coverage. This results in spectrum sharing with the consequences of cross-tier interference from the macrocell user equipment (MUEs) to the femtocell access points (FAPs). This work considers the uplink cross-tier interference management for the cell-edge MUEs (CUEs) in cooperative multi-user multiple input multiple output (MU-MIMO) systems. For better interference management, the CUEs are grouped into clusters and communicate to the macrocell base station (MBS) through a relay node (RN). The linear pre-coders and decoders algorithms for the FAPs, MUEs and CUEs are proposed for effective interference management to minimize the sum mean square error (MSE), subject to the total transmit power constraints. The designed pre-coders and decoders use the pilot-assisted channel estimation to improve the accuracy of the acquired channel state information (CSI). The least-square (LS) and minimum MSE (MMSE) channel estimators are considered. The performance of the system is investigated in terms of the bit error rate (BER) for the linear pre-coders and decoders algorithms with the pilot-assisted channel estimators.